High-performance removal of toxic phenol by single-walled and multi-walled carbon nanotubes: Kinetics, adsorption, mechanism and optimization studies - Dehghani, M.; Mostofi, M.; Alimohammadi, M.; McKay, G.; Yetilmezsoy, K.; Albadarin, A.; Heibati, B.; AlGhouti, M.; Mujawar, Mubarak; Sahu, J. (Elsevier, 2016)
The adsorption capabilities of two nano-sized adsorbents: multi-walled carbon nanotubes (MWCNTs) and single-walled carbon nanotubes (SWCNTs) were investigated for the removal of toxic phenol. The maximum adsorption capacities of MWCNTs and SWCNTs were determined as 64.60 and 50.51 mg/g, respectively. Adsorption kinetics followed the pseudo-second order model for both adsorbents. The optimum conditions using SWCNTs and MWCNTs were pH 6.57 and 4.65, phenol concentration 50 and 50 mg/L, dose 1.97 and 2 g/L and contact time 36 and 56 min, respectively. The results indicated that MWCNTs and SWCNTs were proven as high-performance adsorbents for toxic phenol removal from wastewater.